Interactive stratigraphic structure visualization for seismic data. (October 2018) - Liu, Richen; Chen, Siming; Ji, Genlin; Zhao, Bin; Li, Qiusheng; Su, Mingjun
Abstract: Underground flow path (UFP) plays a significant role in illustrating seismic data and revealing stratigraphic structures presented in the data. It is challenging to interactively illustrate the UFP due to the well-known characteristics of seismic data, i.e., noisy, discontinuous, and low resolution. In this paper, we propose a novel interactive visualization approach to illustrate the seismic data, which employs a bit-array based 3D texture to organize different types of interactions. There are three major merits of the organization scheme: It enables to switch different types of interactions flexibly. It allows to perform progressive seed point tracing to get more accurate UFP structures, and supports different stratigraphic display modes and their flexible switching. The feedback from the domain experts suggests that the proposed approach is capable of better revealing the UFP structure and distribution compared with the existing UFP visualization approaches in this field.